2007 110-CC 4 Stroke Motorcycle Performance Test Using Pertalite, Pertamax and Avgas fuel - Toha, Kamil; Mufarida, Nely Ana; Kosjoko, Kosjoko (Universitas Muhammadiyah Jember, 2023)
Motorcycle performance can be influenced by several factors, one of which is the type of fuel. To find out the performance of the motorbike, testing can be done using tools such as a dynamometer (dynotest). This research aims to determine the performance of a 110 cc 4 stroke motorbike using pertalite, Pertamax and Avgas fuel using a dynotest, which is connected to a computer. The computer will record a graph of the results of changes in power and torque from each fuel test. In this research, the use of pertalite fuel obtained the highest performance results, namely producing maximum power of 8.9 HP at 7036 RPM engine speed with a torque value of 10.40 N*M at 4322 RPM engine speed. Meanwhile, for the use of Pertamax fuel and the use of a mixture of Pertalite fuel with Avgas, the resulting performance tends to be smaller than the performance produced by Pertalite material. So it can be concluded that the use of fuel with an octane value higher than what is recommended by the manufacturer will cause a decrease in the performance of the motorbike engine itself.